The Concept of Withholding Period and Pesticide Residue in Grain Storage - J. A, Adegbola; U. D, Anugwom; F, Awagu; E. A, Adu (Asian Journal of Agriculture and Rural Development, 2012)
This review focuses on pesticides, their unquantifiable benefits to agriculture, pesticide residue, maximum pesticide residue limit, and withholding period in grain storage. It delved into the origin of synthetic pesticide and its introduction to Nigeria in the 1950s, it maintained that pesticide have posed major health and social challenges, and have had negative, unintended, catastrophic, fatal consequences to man, animals, and even the environment especially when instructions on their labels are not adhered to. Again, it maintained that withholding periods are often stipulated on the labels of genuine pesticides, it reiterated that not adhering to the stipulated withholding period can have catastrophic consequences on consumers of grain and grain products. Furthermore, it dwelt on the activities of Nigerian stored Products Research Institute (NSPRI) and National Food Drug Administration and Control (NAFDAC), their mandates and quest to nip pesticide poisoning in the bud. Finally, recommendations were put forward to check the seeming ignorance and dearth of information about pesticide residue limit and withholding period, and dangers that are concomitants of not adhering to these.